Finite Element Modeling of Nanotube Structures : Linear and Non-linear Models - Mokhtar Awang, author; Ehsan Mohammadpour, author; Ibrahim Dauda Muhammad, author (Cham, Switzerland : Springer International Publishing, 2016)
This book presents a new approach to modeling carbon structures such as graphene and carbon nanotubes using finite element methods, and addresses the latest advances in numerical studies for these materials. Based on the available findings, the book develops an effective finite element approach for modeling the structure and the deformation of graphene-based materials. Further, modeling processing for single-walled and multi walled carbon nanotubes is demonstrated in detail.